Application of Nanosilica for inhibition of fines migration during low salinity water injection: Experimental study, mechanistic understanding, and model development. (15th April 2019) - Moghadasi, Ramin; Rostami, Alireza; Hemmati-Sarapardeh, Abdolhossein; Motie, Mohadeseh
Graphical abstract: Highlights: A comprehensive set of core displacement experiments was implemented to evaluate fines migration. The effects of temperature, synthesized Nanosilica, and NaCl concentrations on the permeability ratio are investigated. Disjoining pressure theory is applied to verify the impact of affecting parameters on permeability damage. A simple-to-use model is developed which can be a good candidate in simulating fines migration. Abstract: Low salinity (LS) water injection has emerged as one the most promising methods of improved oil recovery (IOR). However, its performance is often adversely affected by permeability damage due to induced fines migration phenomenon. Although a number of studies considered this phenomenon, no appropriate and global remedy has been proposed to tackle this problem during low salinity water injection. Moreover, no generalized model for simple estimation of permeability damage has been proposed. In the present work, a comprehensive set of core displacement experiments was implemented to evaluate fines migration happening during water injection. In addition, a new Nanosilica available in literature was synthesized and used in the injection brine to measure its impact on the formation damage. Furthermore, the optimum concentration of Nanosilica was determined using electrical conductivity test, which was obtained about 0.1 %wt. Furthermore, the effects of several parameters including temperature, Nanosilica, and NaCl concentrations on the ratio of permeability damage were investigated. The results indicated that, temperature has a decreasing effect on the ratio of permeability damage, while the ratio of permeability damage increases by increasing NaCl and Nanosilica concentrations. It was also found that a sudden increase in injection rate enhances the amount of permeability reduction due to the higher fines migration. Disjoining pressure theory was also applied to verify the impact of affecting parameters on permeability damage. Finally, using a strong mathematical scheme termed as, group method of data handling (GMDH), a simple and accurate model with total prediction error of 6.59%, was established to estimate the ratio of permeability damage. The developed GMDH model is the first model proposed in this field, which can be a good candidate in simulating fines migration happening during low salinity water injection.